2021
DOI: 10.1021/acs.chemmater.0c04105
|View full text |Cite
|
Sign up to set email alerts
|

Displaying Lipid Chains in a Peptide–Polysaccharide-Based Self-Assembled Hydrogel Network

Abstract: Reducing the complex extracellular matrices (ECM) to chemically defined polymer networks represents an attractive avenue for understanding and recapitulating the biology of the ECM. However, while lipids are also important components of ECM, it remains challenging to investigate lipids as a modular functionality in synthetic biomaterials, especially in a self-assembled network. In this study, in order to establish a modular amphiphilic system, lipid-modifications are introduced into a noncovalent hydrogel syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
(71 reference statements)
2
17
0
Order By: Relevance
“…Although the introduction of lipid group into matrix has little effect on the thermodiffusion of the network, the lipid moieties can interact with the hydrophobic compound, thus limiting its thermodiffusion as a free molecule. We have previously shown that Cy5-CsA can bind to KA7-C 16 -starPEG and KA7-C 8 -starPEG with K d values of 30 µ M and 608 µ M, respectively 11 . Eventually, in an amphiphilic matrix, the A T value of Cy5-CsA can be smaller than that in solution, especially in the KA7-C 16 -starPEG/DS and KA7-C 16 -starPEG/SCD hydrogels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the introduction of lipid group into matrix has little effect on the thermodiffusion of the network, the lipid moieties can interact with the hydrophobic compound, thus limiting its thermodiffusion as a free molecule. We have previously shown that Cy5-CsA can bind to KA7-C 16 -starPEG and KA7-C 8 -starPEG with K d values of 30 µ M and 608 µ M, respectively 11 . Eventually, in an amphiphilic matrix, the A T value of Cy5-CsA can be smaller than that in solution, especially in the KA7-C 16 -starPEG/DS and KA7-C 16 -starPEG/SCD hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Although the introduction of lipid group into matrix has little effect on the thermodiffusion of the network, the lipid moieties can interact with the hydrophobic compound, thus limiting its thermodiffusion as a free molecule. We have previously shown that Cy5-CsA can bind to KA7-C16-starPEG and KA7-C8-starPEG with Kd values of 30 µM and 608 µM, respectively 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] However, the low solubility of these nontherapeutic alkyl chain may lead to a poor bioavailability such as stearic acid and arachidic acid. [ 22 ] In this study, we introduced RT sensitizer NIA as a hydrophobic core into a system and synthesized an amphipathic peptide, while the decrease in solubility is unobserved.…”
Section: Resultsmentioning
confidence: 99%